Samba de Véio da Ilha do Massangano: quando a terra treme - Barbosa, Alan Silva (2024)
Samba de Véio is a spectacularized form of Samba de Rancharia – originated from reisado, which takes place on Massangano Island in Petrolina-PE in January and which has samba as its music. Samba de Véio appears as an outspread of Samba de Rancharia, encouraged by media actions that aimed to record and broadcast video programs presenting interactions between rural communities, harvest festivals and riverside celebrations. In view of this, the samba played and danced in January at the reisado, now known as Samba de Rancharia by the community, appears in media, formatted and suitable for commercial elements, with the name Samba de Véio, due to the members of the group being adults and/or elderly. This is an ethnographic research with participant observation, conducted from November 2020 to July 2023. The epistemological and theoretical dimension of the thesis used studies on musical performance, identity, territory and territoriality, articulating areas such as ethnomusicology, anthropology and sociology. Thereby, this thesis discusses how the musical performance of Samba de Véio from Massangano Island articulates elements of cultural identity from Massangano population. Searching for possible answers to the question presented, I literally entered the territory, as during fieldwork I acquired a house on the island. This fact changed the methodology used for the research, but also presented some problems in data interpretation. Therefore, the researcher, now a resident and neighbor of the samba dancers, experienced this duality. In view of this, the thesis focuses on the problems of media interference and the spectacularization of Samba de Véio, proposing, from ethnomusicology, to problematize the sound recordings made in the demonstration's studio, the political partisan interference and, above all, some invisibilities, for example, women in samba who, despite having an important role in maintaining the manifestation, do not have a prominent place in research and studies on Samba de Véio.